Enhancement of the efficiency of activities of development companies, considering the application of conceptual approaches to the realization of projects for cottage construction - Kishchenko, T. Ie. (Ways to Improve Construction Efficiency, 2020)
The article discusses the dominant conceptual approaches of real estate companies to the implementation of cottage construction projects. Listed are the goals that can be guided by a real estate company when launching a cottage development project. The sequence of actions and options for attracting investments are determined in accordance with the conceptual approach chosen by the development company for the implementation of the cottage construction project. It is determined that the main factors of efficiency and success of the cottage is its location, price and construction concept. Developers are trying to create cottage towns of different shapes and formats using different conceptual approaches to this process, as cottage towns have many advantages over unorganized construction: it is to create an environment where you can feel unsafe and comfortable, but at the same time among people in your circle; this is the presence of a general plan of construction and a common architectural concept; this is a living and leisure infrastructure that allows you to get the most comfort without leaving the town limits. The article discusses the dominant conceptual approaches of developers to the implementation of cottage construction projects. The goals that the developer company is launching when launching a cottage farm project are identified, and features that will affect the selection of project team members, market research, marketing, design, construction, financing, accounting, property management. Features of development in the implementation of different conceptual approaches to the construction of cottage villages related to the choice of the target segment, marketing, choice of design and architectural solutions, financing structure of the object, management of the finished object, legal registration of ownership rights.